Unlocking Human Dignity: A Plan to Transform the US Immigrant Detention System1. (June 2015) - Unknown
Unlocking Human Dignity: A Plan to Transform the US Immigrant Detention System addresses one of the most troubled features of the US immigration system and highlights the need for fundamental changes to it. The report comes six years since the inception of the Obama administration's detention reform initiative. In the interim, the number of immigrant detainees per year has risen to more than 400, 000, the administration has opened immense new family detention centers, and the overwhelming majority of persons in the custody of the Department of Homeland Security (DHS) have remained in prisons, jails and other secure facilities where they are subject to standards designed for criminal defendants and, in many ways, treated more harshly than criminals. The report's overarching recommendation is that the US immigrant detention system be dismantled and replaced with a network of supervised release, case management, and community support programs, designed to ensure court appearances. It recognizes that detention may be necessary for short periods and in certain cases, but it rejects detention as a central immigrant "management" tool, and argues that detention should only be used as a last resort if less harmful strategies and programs—viewed on a continuum beginning with the least restrictive and moving to release programs with different levels of supervision, monitoring, and support— cannot reasonably ensure court appearances or (in rare cases) protect the public. It opposes the detention of pregnant and nursing women, bona fide asylum seekers, the very ill, the disabled, the elderly, and other vulnerable persons. It calls for the substantial contraction of detention facilities and "bed space." As the first step in this process, the report urges Congress to commission a comprehensive study on the benefits, challenges, cost, and time frame for creating a civil immigration detention system. It also proposes that the administration create a full menu of court compliance programs, with varying degrees of supervision, reporting, oversight and monitoring. In order to realize this vision, it offers several additional recommendations. The Obama administration should desist from using detention as a "deterrent" to illegal migration and de facto refugee flows. DHS should close its family detention centers in favor of community-based supervision and support programs for immigrant families. The vast majority of families would appear for removal proceedings with appropriate orientation, supervision and community support. The growth of an immense family detention infrastructure will not (as intended) deter imperiled persons from seeking refuge in the United States, but will invariably lead to the return of de facto refugees to their persecutors in violation of international law. Congress should pass legislation to repeal mandatory detention in all but the most egregious criminal and national security cases. US mandatory detention laws cover lawful permanent residents, asylum seekers, petty offenders, and persons with US families and other enduring ties to the United States. By definition, they prevent individualized release determinations based on family ties, employment, housing, criminal history, and other factors. In the overwhelming majority of cases, immigration judges or judicial officers should be permitted to consider the full range of equities and release options for persons in removal proceedings, whether formal court proceedings or non-court, administrative and summary processes. Private corporations should have a more limited, regulated and modest role in a shrinking detention system. The federal government has increasingly ceded responsibility for detention to entities whose loyalties run to their shareholders, not the common good. By some estimates, for-profit prison corporations administer more than 60 percent of the "beds" in the US immigrant detention system. Rather than expanding its reliance on for-profit prison companies, the federal government ought to decrease the use of detention, develop greater government expertise, and strengthen oversight of private contractors. Detention reform should include a significant expansion of Alternative to Detention programs (ATD). Detention should only be used sparingly, for brief periods (when necessary), and as a last resort when less restrictive strategies cannot reasonably ensure appearances during the adjudication and removal process and cannot protect the public. ATD programs can offer effective, humane alternatives to detention. However, they should not be used to expand detention capacity. Like detention, intensive reporting and monitoring programs can stigmatize and incapacitate persons. If necessary, ATD programs should be treated as a form of custody, which would open them to mandatory detainees. Immigration and Customs Enforcement (ICE) should undertake a comprehensive analysis of its information systems. The proposed review should identify the information ICE tracks on those who are subject to its custody; how, when, and which officials collect, enter, and can access this information; its quality control procedures; and the accessibility of information to congressional oversight committees, government watchdog agencies, relevant ICE officials, and the public. Detained immigrants—those who do not qualify for release or ATD programs—should be held in non-penal settings which reflect the conditions of normal life to the extent feasible. DHS should provide generous access to international organizations, faith-based groups, nongovernmental organizations (NGOs) and the press, to all of its facilities. Immigration judges should adjudicate removal cases now handled through administrative, informal and non-court processes, and should make release and custody determinations soon after their detention for all persons in DHS custody. They should also regularly revisit custody decisions for detainees. However, these responsibilities—added to an immense yearly workload and a daunting backlog of more than 440, 000 cases—will require increases in funding and staffing by an order of magnitude. As it stands, the immigration court system receives less than two percent of the combined funding of Customs and Border Protection (CBP) and ICE. The cost of "right-sizing" the immigration court system may well be offset by reductions in DHS detention funding and diminished federal court expenses from habeas corpus petitions. Unrepresented, indigent persons in removal proceedings should be provided with legal representation at the government's expense. As numerous studies have revealed, legal counsel is one of the most important factors, even more important than the strength of the underlying legal claim, in influencing asylum and other case outcomes. Representation also increases court appearance rates and leads to decreased overall costs to the government due to reduced use of detention, more efficient court proceedings, and less frequent placement of the children of detainees in foster care. More importantly, it contributes to the right decisions being made under the law. Migration and Refugee Services of the US Conference of Catholic Bishops (MRS/USCCB) and the Center for Migration Studies (CMS) approach the detention of immigrants from a pastoral perspective. Each day US Catholic institutions minister to detained immigrants, represent them in removal proceedings, tend to the material and spiritual needs of their families, and witness the pain of traumatized children and the anguish of divided families. Because of the detention system's devastating effect on the lives of millions of persons each year, MRS/USCCB and CMS strongly support the transformation of this system and urge the Obama administration and Congress to proceed with the proposed reforms with all deliberate haste.